Operating systems : design and implementation - Tanenbaum, Andrew S., 1944- (Pearson/Prentice Hall, 2006)
Featuring an introduction to operating systems, this work reflects advances in OS design and implementation. Using MINIX, this book introduces various concepts needed to construct a working OS, such as system calls, processes, IPC, scheduling, I/O, deadlocks, memory management, threads, file systems, security, and more.